TREATING ITP: What are the options in the era of new guidelines and new drugs? - Pantić, Nikola M; Suvajdzic Vukovic, Nada (Medicinski podmladak, 2020)
Primary immune thrombocytopenia (ITP) is an autoimmune disease characterised by isolated thrombocytopenia. Treating ITP may be challenging since different treatment modalities are available. While choosing the suitable option for every patient a physician should take into account both patient’s medical characteristics and wishes. The first line treatment options include: corticosteroids, intravenous immunoglobulins and intravenous anti-D immunoglobulin. Second line treatment options comprise medical (thrombopoietin receptor agonists, rituximab, fostamatinib, azathioprine, cyclophosphamide, cyclosporin A, hydroxychloroquine, mycophenolate mofetil, danazol, dapsone, vinca-alcaloids) and surgical (splenectomy) approach. However, there are some treatment gaps which remain uncovered with existing treatment modalities. Therefore, development of novel therapeutic strategies is required. The aim of this review is to provide an illustrative overview of novel treatments for adult ITP.